2018
DOI: 10.1093/cid/ciy987
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Active and Latent Tuberculosis in Children and Adolescents in Tibetan Schools in India: The Zero TB Kids Initiative in Tibetan Refugee Children

Abstract: Background Tuberculosis (TB) prevalence is high among Tibetan refugees in India, with almost half of cases occurring in congregate facilities, including schools. A comprehensive program of TB case finding and treatment of TB infection (TBI) was undertaken in schools for Tibetan refugee children. Methods Schoolchildren and staff in Tibetan schools in Himachal Pradesh, India, were screened for TB with an algorithm using symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 24 publications
2
33
0
Order By: Relevance
“…Despite the complexity in quantifying where M tuberculosis transmission occurs in children at the population level, understanding this key question is essential to design appropriate and effective public health programmes to detect, diagnose, and treat children with tuberculosis. 13 studies [14][15][16][17][18][19][20][21][22][23][24][25][26] published between 2003 and 2018 that made use of diverse methodologies and designs shed light on this topic. This description is specific to the type of study, and is thus described for each study type in later sections.…”
Section: Epidemiological Evidence: Investigating Where Paediatric Tubmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the complexity in quantifying where M tuberculosis transmission occurs in children at the population level, understanding this key question is essential to design appropriate and effective public health programmes to detect, diagnose, and treat children with tuberculosis. 13 studies [14][15][16][17][18][19][20][21][22][23][24][25][26] published between 2003 and 2018 that made use of diverse methodologies and designs shed light on this topic. This description is specific to the type of study, and is thus described for each study type in later sections.…”
Section: Epidemiological Evidence: Investigating Where Paediatric Tubmentioning
confidence: 99%
“…Five similar studies that were not included in this review 18 also found similar results (table 1). [19][20][21][22][23] A community-based survey of 3170 children from Malawi was done. 19 Using mixture analysis of tuberculin data, the authors found that 1•1% of all children were infected.…”
Section: Tuberculosis Infection Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…Dorjee et al, reported a latent TB infection prevalence of 18% and 54% among secondary school children and staff respec-B. A. Alex-Hart et al These researchers equally found 46 cases of TB disease and one case of extensive drug resistant TB amongst the children[8]. Though these studies were done outside Nigeria, they however showed the magnitude of the global childhood TB burden among school children and the need to include the school communities in the active TB case finding.…”
mentioning
confidence: 99%